A kinematic analysis of high-speed treadmill sprinting over a range of velocities - Kivi, D. M. R.; Maraj, B. K. V.; Gervais, P. (Medicine & Science in Sports & Exercise, 2002)
The purpose of this study was to measure changes in stride characteristics and lower-extremity kinematics of the hip and knee as a function of increasing treadmill velocity, at velocities ranging from submaximal to near maximal. METHODS: Six power/speed athletes experienced at sprinting on a treadmill performed trials at 70%, 80%, 90%, and 95% of their previous individual maximum velocity, with video data collected in the sagittal view at 60 Hz. RESULTS: Significant differences were seen in stride frequency (70%, 80%, P < 0.01; 90%, P < 0.05), stance time (70%, 80%, P < 0.01; 90%, P < 0.05) flight time (70%, P < 0.01; 80%, P < 0.05), hip flexion angle (70%, P < 0.01), hip flexion angular velocity (70%, P < 0.01), hip extension angular velocity (70%, 80%, P < 0.01), knee flexion angular velocity (70%, 80%, P < 0.01), and knee extension angular velocity (70%, P < 0.01), as compared with the near maximum (95%) velocity. Coefficient of variation (CV) values showed that the positional variables at the hip and knee were more variable at faster test conditions, indicating that kinematic changes occur as a function of increased treadmill velocity. CONCLUSIONS: The results indicated that at slower velocities, there were differences in the stride characteristics and lower-extremity kinematics while sprinting on a treadmill. As the velocity approached near maximum mechanical breakdown was seen, suggesting that velocities greater than 90% should be used selectively during treadmill training.